Thoroughbred Mare Reproduction in Eclipse Stud and Stable Boyolali - Alma Shabrina; Tetty Barunawati Siagian (UNIVERSITAS ISLAM LAMONGAN, 2022)
Thoroughbred is a type of horse that is widely used for racing. Breeding Thoroughbred aims to produce Thoroughbred offspring that have superiority and better performance than their parents. The selection of Thoroughbred females for breeding breed is based on achievement and pedigree. In order to do so, basic information about the reproduction of female Thoroughbred horses is needed. Observation was conducted to provide information about the reproductive data of Thoroughbred mares in Eclipse Stud and Stable Boyolali. The observation focused on 19 female horses that were still productive. Parameters observed for reproduction of Thoroughbred mares in Eclipse Stud and Stable Boyolali were the average age at first mating, first estrus, length of estrus, estrus cycle, estrus symptoms, and post parturition estrus. The results of observations of reproduction of Thoroughbred mares in Eclipse Stud and Stable Boyolali were; first mating was at the age of 3 years, the first estrus was at the age of 15 months, the length of estrus was 4 days, the estrus cycle lasted for 21 days, the duration of gestation was ± 11 months and Ultrasound pregnancy detection was performed on day 18.